Correction: Corrigendum: DNA damage response inhibition at dysfunctional telomeres by modulation of telomeric DNA damage response RNAs - Francesca Rossiello (Nature Portfolio, 2017)
Nature Communications 8: Article number: 13980 (2017); Published: 27 February 2017; Updated: 13 April 2017 In Supplementary Fig. 3d, the two columns of DAPI images associated with pATM and pS/TQ images were inadvertently swapped. The correct version of this figure appears below.